2017
DOI: 10.1016/s1474-4422(17)30332-0
|View full text |Cite
|
Sign up to set email alerts
|

24-month intervention with a specific multinutrient in people with prodromal Alzheimer's disease (LipiDiDiet): a randomised, double-blind, controlled trial

Abstract: SummaryBackgroundNutrition is an important modifiable risk factor in Alzheimer's disease. Previous trials of the multinutrient Fortasyn Connect showed benefits in mild Alzheimer's disease dementia. LipiDiDiet investigated the effects of Fortasyn Connect on cognition and related measures in prodromal Alzheimer's disease. Here, we report the 24-month results of the trial.MethodsLipiDiDiet was a 24-month randomised, controlled, double-blind, parallel-group, multicentre trial (11 sites in Finland, Germany, the Net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
228
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 192 publications
(246 citation statements)
references
References 37 publications
16
228
0
2
Order By: Relevance
“…Also in mild AD, Scheltens et al [6] showed an improvement on the neuropsychological test battery memory domain and electroencephalography functional connectivity in the delta band after 24 weeks. In contrast, a recent large study by Soininen et al [26] investigated the effect of Souvenaid in prodromal AD subjects, a population close to the current population with MCI or mild dementia due to AD. In this study, a positive effect on the clinical dementia rating sum of boxes and hippocampal and ventricular volume on MRI was found after 2 years of treatment, although the effects were not yet observed at the study's 1-year half-way point.…”
Section: Discussionmentioning
confidence: 98%
“…Also in mild AD, Scheltens et al [6] showed an improvement on the neuropsychological test battery memory domain and electroencephalography functional connectivity in the delta band after 24 weeks. In contrast, a recent large study by Soininen et al [26] investigated the effect of Souvenaid in prodromal AD subjects, a population close to the current population with MCI or mild dementia due to AD. In this study, a positive effect on the clinical dementia rating sum of boxes and hippocampal and ventricular volume on MRI was found after 2 years of treatment, although the effects were not yet observed at the study's 1-year half-way point.…”
Section: Discussionmentioning
confidence: 98%
“…Despite several systematic reviews and meta-analyses of observational studies in recent years,6,9 no firm conclusions can be drawn. Intervention studies on diet modification and/or supplementation do not show an effect,1013 with one exception 14. Most previous studies on diet and dementia had a short follow-up, typically less than 10 years where reverse causation may bias results as dietary behavior and nutrient intake may be altered during the long preclinical period of dementia 15…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has supplemented for 2 years patients with precursor signs of Alzheimer's disease. The active ingredient was composed of omega-3 fatty acids, uridine, choline, phosphates and B vitamins but this supplementation had no effect on cognitive scores compared to the placebo (Soininen et al, 2017). Thus, there is currently no consensus on the effectiveness of a nutritional strategy to prevent or limit the progression of cognitive decline.…”
Section: Evidence Of Effective Prevention Strategiesmentioning
confidence: 99%